Implementation of hallucination strategies - A case study on adolescent with hearing hallucinations - Firdaus, Rosalia; Hernawaty, Taty; Suryani, Suryani; Banda, Kondwani Joseph (Palembang MediRose Publisher, 2023)
Background: Schizophrenia stands out as a prominent type of psychosis among various mental disorders. Auditory hallucinations, a prevailing symptom, particularly affect patients with primary psychotic disorders, showcasing a lifetime prevalence rate of 60-80% within the spectrum of schizophrenia disorders. Objective: This case study presents data and insights concerning the management of nursing challenges linked to auditory hallucinations. Case: A 17-year-old male was admitted to the psychiatric hospital after being involved in a violent incident with his family. He contended that he was compelled by an external entity to carry out this act. When in his room, the patient exhibits pronounced hallucinatory behavior, including tangential thinking, inability to concentrate during conversations, physically covering his ears in fear, and restless pacing, occasionally attempting to conceal himself under the bed. The nurse employs intervention strategies to address the client’s hallucinations, incorporating methods to gain control over them. These strategies involve encouraging breaks, fostering engagement in positive activities, closely monitoring the patient, and providing education on consistent medication adherence. Conclusions: After a nine-day period of effectively managing the hallucinations, the patient gains substantial control over them, thereby leading to the resolution of his hallucinatory issues. This research holds potential as a valuable resource for psychiatric nurses in devising interventions within psychiatric hospital settings. Furthermore, it can serve as a foundational component for the evaluation of psychiatric facilities in their provision of effective interventions for patients with psychiatric conditions